Study to Know the Impact of Ayurvedic Lifestyle on Dark Circles Around Eyes - P, Ankita; Harti, Shivakumar; Rao, Mangalagowri (Current Traditional Medicine, 2021)
Background: The dark circles under the eyes are a very common and frustrating cosmetic grievance in both males and females, especially among the stress prone population. Due to various reasons, the skin becomes very thin and dry, leading to the visible appearance of veins. This makes the skin appear very dark. Possible causes include excessive pigmentation, thin and luminous lower eyelid, lack of sleep, excessive fatigue, heredity, allergic disorders and aging. Dark circles come under the broad umbrella of features of aggravation of Vata like blackish discoloration (Karshnya), Dark coloration (Shyavata), which can also be categorized under disease predominant in Vata (Vata Nanatmaja Vikara). In spite of its prevalence and cosmetic importance, there are very few reported works regarding dark circles. Objectives: This study was an attempt to find the most probable and commonest factor that influences dark circles so that modifications can be made in lifestyle as mentioned in Ayurveda in the form of daily regimen (Dinacharya) and Night regimen (Ratricharya). Methods: 30 subjects (20-40 years) each with or without dark circles were registered and the Case Control survey was conducted using a standard questionnaire. A questionnaire was prepared comprising different processes of daily regimen (Dinacharya vidhis) as per ideal Ayurveda lifestyle. The perceived stress scale that may influence the development of dark circles was also included in the study. The data collected were computed in the excel sheet. The data were analyzed by applying the odds ratio and Chi-square test. Results: A positive relationship between intake of ghee and milk and absence of dark circles was observed, and the odd’s ratio was calculated as 1.5 and 3.54, respectively. The subjects practicing Yoga were found less affected by dark circles; the odds ratio was calculated as 3.7. Stress was moderately high among the subjects having dark circles. Conclusion: The present study shows that individuals following Ayurvedic lifestyle in the form of processes of daily regimen (Dinacharya vidhis) like head and feet massage with oil, Yogic practices, taking milk and ghee in the diet regularly and taking adequate sleep, are less prone to loss of luster in the form of dark circles around the eyes.
Keywords: daily regimen (Dinacharya)